Antimicrobial resistance of gram-negative bacteria: A six-year longitudinal study in a hospital in Saudi Arabia - Jaffar A. Al-Tawfiq; Ali A. Rabaan; Justin V. Saunar; Ali M. Bazzi (Elsevier, 2020)
Introduction: Increasing prevalence of antimicrobial resistance is a major concern especially in light of lack of new antimicrobial agents. Here, we present antibiotic resistance pattern of gram-negative bacteria (GNB) over six years (2013-2018) in a hospital in Saudi Arabia. Materials and Methods: The study included a report of the cumulative antibiogram of GNB. Interpretation of the antibacterial susceptibility tests was based on the Clinical and Laboratory Standards Institute guidelines and VITEK® 2 system. Results: There was a total of 32,890 GNB isolates and the most common were: Escherichia coli (69.8%), Klebsiella pneumoniae (17.2%) and Pseudomonas aeruginosa (12.8%). Antimicrobial susceptibility of P. aeruginosa and E. coli did not change overtime, however, susceptibility to ceftazidime decreased from 92% to 85% in P. aeuroginosa. Yearly antimicrobial susceptibility did not change significantly overtime for K. pneumoniae. ESBL isolates among K. peumoniae and E. coli was about 26% and 20%, respectively (p = 0.0068). For ESBL E. coli, the least effective antibiotics were ciprofloxacin (26%) and trimethoprim-sulfamethoxazole (34%). For ESBL K. pneumoniae, gentamicin, ciprofloxacin, trimethoprim-sulfamethoxazole, and nitrofurantoin had poor activity. For K. pneumoniae, both ciprofloxacin (90%) and trimethoprim-sulfamethoxazole (86%) had better coverage than for E. coli. K. pneumoniae showed less susceptibility to nitrofurantoin than E. coli (20% vs. 92%). Conclusion: Antibiotic resistance among P. aeruginosa and E. coli did not change overtime (2013-2018) and the rate of ESBL-producing E. coli and K. pneumoniae was high. Thus, continued surveillance is needed. Keywords: Antibiotic resistance, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa